THE EFFECT OF MINDFULNESS ON THE INSECURITY OF STUDENTS IN THE ISLAMIC COUNSELING AND GUIDANCE PROGRAM AT UIN NORTH SUMATRA - Evi Yuliani; Nurhanifah Nurhanifah (Jurnal Konseling Pendidikan Islam, 2026)
Feelings of insecurity among students are characterized by a sense of insecurity, low self-esteem, and self-doubt, which can hinder academic and professional readiness. Mindfulness is viewed as one of the psychological factors that has the potential to help individuals manage negative self-evaluation in a more adaptive manner. This study aims to analyze the effect of mindfulness on feelings of insecurity among students in the Islamic Counseling and Guidance (BPI) at UIN North Sumatra. This study employs a quantitative approach with a correlational design. The sample consists of 100 BPI students from the 2022–2025 cohorts selected via purposive sampling. Data were collected using a mindfulness scale adapted from the Five-Factor Mindfulness Questionnaire (FFMQ) based on previous research and an insecurity scale whose validity and reliability had been tested, and were then analyzed using simple linear regression with the aid of SPSS version 22. The results of the study indicate that mindfulness has a negative and significant effect on feelings of insecurity (Sig. 0.000 < 0.05) with a regression coefficient of -0.814. The coefficient of determination (R²) value of 0.390 indicates that mindfulness contributes 39% to the variation in students’ feelings of insecurity. This finding suggests that increasing mindfulness has the potential to reduce levels of insecurity and support the academic and professional readiness of BPI students.